Evaluation of school-based prevention program in Turkey: Results of a 24-month study - Dulgergil, Coruh Turksel; Ercan, Ertugrul; Colak, Hakan (European Journal of Dentistry, 2016)
Objective: In this paper, cavity experiences of children with different levels of eruption and cavity activities that are enrolled at an elementary school with semi-rural characteristics in Kırıkkale Provincial center were monitored for 2 years after a variety of protective applications. Materials and Methods: Three hundred and twenty-two children at the age of 7–11 were included in this study. Children were grouped as follows according to their cavity experiences and applications done: Group 1 - control group (with or without cavities) – was given hygiene training only; Group 2 - with medium level cavity activity (2–4 cavities in average) – oral hygiene training + surface restoration applied; Group 3 - children with 2–4 cavities on average – oral hygiene training + professional flour gel applied; Group 4 - children with 2–4 cavities in average – oral hygiene training + flour gel applied with brush; Group 5 - children with extreme cavity activity (children with 5 or more cavities) – oral hygiene training + surface restoration + professional flour gel combination applied. Results: At the end of the 2nd year, 277 children were reached. The increase of number of cavities in permanent teeth was determined as 35%, 0%, 1%, 0%, and 7% in groups 1–5, respectively. The difference between groups was found to be significant (Chi-square analysis, Pearson Chi-square = 27.002, P < 0.01). Conclusion: These findings have showed that, in Kırıkkale Provincial center, some cavity-preventive measures such as surface restoration and gel applications, along with hygiene training, could provide optimum protection for school-age children.
Keywords: Atraumatic restorative treatment surface restoration; flour gel; gel application with brush; protective measures; tooth cavity